China and the West a pragmatic Confucian's view - Yao, Yang 1964- (Palgrave Macmillan, 2023)
"This is an authored volume of Dr. Yao's 'big-picture' writings on China and the West, translated by David Ownby. Those writings are selected from his writings as a public intellectual, reflecting his thought on China's path of modernization and the effort to rebuild a political philosophy based on Confucianism, his interpretation of China's political system and his prescriptions to improve it. A moderate, yet influential scholar, Yao's work has had great influence on Chinese social and economic policymakers; his project of renewing China's traditional value system is an important position, as Chinese reforms begin to focus on equity and inclusion. In an engaging, at times personal, and thoughtful volume, Dr. Yao's vision of a gentler Chinese society will interest Sinologists, political scientists, and journalists."--
"Translated by David Ownby"--Title page verso
Keywords: Zhong guo gong chan dang; Geschichte 2000-; Sozioökonomischer Wandel; Politik; Konfuzianismus; China; Confucianism and state / China / 21st century; China / Relations / Western countries; Western countries / Relations / China; China / Politics and government / 2002-; China / Foreign relations / 21st century; Philosophy, Confucian; Confucianisme et État / 21e siècle; Occident / Relations / Chine; Chine / Relations extérieures / 21e siècle; Philosophie confucéenne; Confucianism and state; Diplomatic relations; International relations; Politics and government; Western countries; Since 2000; Aufsatzsammlung